Measurement of Oil Palm LAI by Manual and LAI-2000 Method - Awal, Md. Abdul; Wan Ismail, Wan Ishak (Asian Network for Scientific Information, 2008)
In this study, accurate Leaf Area Index (LAI) of different palm age groups were determined by manual (direct) method. Optical methods for quantifying variation in LAI of different palm ages were evaluated using LAI-2000 Plant Canopy Analyser (PCA) as an indirect method. In the manual method, LAI values obtained were 0.69, 1.11, 2.38, 2.49, 3.41, 3.83, 4.05 and in the indirect method LAI values obtained were 1.75, 1.4, 1.14, 1.42, 2.87, 1.89, 3.05 for 2, 3, 6, 7, 9, 12 and 16 year old palms, respectively. Results showed that the PCA LAI values were overestimated for immature palms but underestimated for mature palms. The PCA LAI values were overestimated by 30.8-153% for 2 to 3-year old palms and underestimated by 24-52% for beyond 6-year old palms as compared to manual measurement. The relationship between palm age and LAI was also established in this study. A strong linear relationship between direct LAI and palm age was observed with a correlation coefficient, R = 0.90. However, the relationship between PCA LAI and palm age was weak and not significant. A relationship was observed between PCA LAI and direct LAI with a correlation coefficient of R = 0.57. The study shows that it was possible to rapidlyÂ determineÂ LAIÂ usingÂ theÂ LAI-2000Â PlantÂ CanopyÂ Analyser.Â ThisÂ rapidÂ and non-destructive method saves labour when compared to manual measurements. However, this instrument gave inconsistent of LAI values in respect to oil palm age.